Copolymerization of Sulfur Chains with Vinyl Functionalized Metal−Organic Framework for Accelerating Redox Kinetics in Lithium−Sulfur Batteries. Issue 21 (7th April 2022) - Zeng, Qinghan; Li, Xin; Gong, Wei; Guo, Sijia; Ouyang, Yuan; Li, Dixiong; Xiao, Yingbo; Tan, Chao; Xie, Lin; Lu, Haibin; Zhang, Qi; Huang, Shaoming
Abstract: Lithium−sulfur batteries (LSBs) are regarded as one of the most promising candidates for energy storage devices. However, the severe shuttling effect of soluble polysulfides (PSs) limits its further application. Metal−organic frameworks (MOFs) have emerged as a new kind of sulfur host for their talents in confining and trapping PSs. However, the shuttle effect has not been fully stressed as a significant drawback for most MOFs that leads to sluggish redox kinetics, resulting in low specific capacity and short lifetime, especially at high sulfur loading. In this work, a MOF‐sulfur copolymer (CNT@UiO‐66‐V‐S) is elaborated by copolymerization of sulfur with vinyl functionalized MOFs. Systematic electrochemical experiments and in situ Raman spectroscopy analysis indicate that the cathode exhibits a radical reaction mechanism and can accelerates LiPSs conversion. The CNT@UiO‐66‐V‐S cathode delivers over 100% improved discharge capacity and lowers decay rate at both low and high (5.6 mg cm –2 ) sulfur loadings compared to the physically mixed MOF/S cathode. The strategy of MOF‐sulfur copolymerization provides a new solution for promoting reaction kinetics and tackling the shuttle effect, and is expected to inspire the design of advanced sulfur hosts applied for high‐performance LSBs. Abstract : A MOF‐sulfur copolymer (CNT@UiO‐66‐V‐S) is designed and synthesized by chemically grafting the sulfur chains with the vinyl functionalized MOFs (UiO‐66‐V), which accelerates LiPSs conversion and restrains the shuttle effect via the faster radical reaction of chemically grafted sulfur chains. Moreover, CNT@UiO‐66‐V‐S cathode delivers obviously improved battery performance compared to the traditional MOF/S composite cathode at both low and high sulfur loadings.